Method for preparing high-permeability polyamide nanofiltration membrane by using crystal template
By using crystal templates to prepare composite polyamide nanofiltration membranes, the problem of reduced selectivity of nanofiltration membranes when improving permeability is solved, and the synchronous improvement of high permeability and high ion selectivity is achieved, which is suitable for a variety of industrial applications.
Patent Information
- Application Number
- CN202411928610.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-12-25
AI Technical Summary
When existing nanofiltration membranes improve permeability, they often lead to reduced membrane selectivity, limiting their development and application in industrial applications.
By using crystal templates to prepare composite polyamide nanofiltration membranes, the surface structure and pore size distribution of the functional layer are optimized, and the permeability and ion selectivity of the membrane are improved.
The synchronous improvement of high permeability and high ion selectivity has been achieved. The retention rate of sodium sulfate can reach more than 98.5%, and the water flux can reach more than 14L/(m2·h·bar). It is suitable for hard water softening and seawater desalination pretreatment.
Smart Images

Figure CN119588182A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of membrane preparation methods, and in particular relates to a method for preparing a high-permeability polyamide nanofiltration membrane by utilizing a crystal template. Background Art
[0002] Membrane separation technology is a separation method with low energy consumption, high precision, high flux and simple operation. It is widely used in the fields of medicine, biology, water treatment, chemical industry and other industries, and has huge social and economic benefits. Among them, nanofiltration membrane is a new type of separation membrane with a pore size between reverse osmosis membrane and ultrafiltration membrane. It has nano-level filtration accuracy and large permeation flux, which can greatly improve membrane separation efficiency.
[0003] Although ideal nanofiltration membranes have high permeability flux and molecular / ion separation selectivity, the current preparation of nanofiltration membranes still faces a serious trade-off effect between permeability and selectivity. For example, increased permeability will inevitably lead to reduced membrane selectivity, which greatly limits its development and application. Therefore, how to improve the membrane trade-off effect and simultaneously improve the membrane's permeability and selectivity is the key to preparing high-performance nanofiltration membranes.
[0004] Based on the above analysis, the present invention relates to a polyamide nanofiltration membrane that selectively separates monovalent and divalent anions, which can simultaneously improve the water permeability and ion selectivity of the membrane. The present invention is simple to operate, and a composite polyamide nanofiltration membrane is prepared by a method of supramolecular induced crystal growth and traditional interfacial polymerization. The optimized functional layer is firm and effective, has a special surface structure and a narrow pore size distribution feature, and effectively improves the permeability and monovalent and divalent ion selectivity of the membrane, which is of great significance for the application of polyamide-based composite nanofiltration membranes in hard water softening or seawater desalination pretreatment and other related fields. Summary of the invention
[0005] The present invention is aimed at the above technical analysis and existing problems, and provides a method for preparing a highly permeable polyamide nanofiltration membrane using a crystal template, which has the characteristics of large water permeability, high permeability flux and good separation performance. First, weigh the sodium hyaluronate (HA-CD) powder modified by β-cyclodextrin and place it in a conical flask, then add deionized water to dissolve it to obtain a HA-CD solution; weigh potassium chloride (KCl) powder and add it to the HA-CD solution, stir to dissolve it; weigh piperazine monomer (PIP) and dissolve it in the aforementioned mixed solution, that is, a mixed aqueous phase solution; at the same time, use n-hexane solution to dissolve trimesoyl chloride (TMC) as an oil phase solution. The polymer base membrane is immersed in the aqueous phase solution for a period of time and then drained, and then placed in an oven for heat treatment. After a period of time, the treated polymer base membrane is taken out for standby use. Finally, the oil phase solution is poured on the surface of the base membrane for interfacial polymerization reaction, and the residual oil phase solution is removed after a period of reaction, and it is placed in an oven for drying treatment. After drying, it is stored in deionized water to obtain a composite polyamide nanofiltration membrane.
[0006] To implement the above technical solution, including.
[0007] Step 1: Weigh β-cyclodextrin-modified sodium hyaluronate (HA-CD) powder and place it in a conical flask, then add deionized water to dissolve it to obtain a HA-CD solution, wherein the mass concentration of the HA-CD solution is 0 to 1.0%.
[0008] Step 2: Weigh potassium chloride (KCl) powder and add it to the HA-CD solution, stir to dissolve it, and the mass volume concentration of KCl in the mixed solution is 0-10 g / L.
[0009] Step 3: Weigh piperazine monomer (PIP) and dissolve it in the above mixed solution to obtain a mixed aqueous phase solution, wherein the mass concentration of PIP is 0.4%.
[0010] Step 4: prepare a TMC oil phase solution with a certain mass volume concentration using n-hexane solution, wherein the mass concentration fraction of TMC is 0.1%.
[0011] Step 5: Immerse the polymer-based membrane in the mixed aqueous phase solution for 5 minutes and drain for 1 minute.
[0012] Step 6: Place the base film from the previous step in an oven for heat treatment. The temperature of the oven is set to 40-80° C. and the heat treatment time is 10 minutes.
[0013] Step 7: Pour the prepared TMC oil phase solution onto the surface of the base membrane in step 6 to carry out interfacial polymerization reaction. After a period of reaction, pour out the remaining unreacted TMC solution to obtain a primary polyamide nanofiltration membrane. The reaction time is 2 minutes.
[0014] Step 8: Heat treatment: Place the primary polyamide nanofiltration membrane obtained in step 7 in an oven for heat treatment. At this time, the temperature of the oven is set to 65° C. and the heat treatment time is 15 min to obtain a composite polyamide nanofiltration membrane.
[0015] Step nine, placing the composite polyamide nanofiltration membrane in deionized water for storage.
[0016] The polymer-based membrane material is preferably one of polyethersulfone (PES), polysulfone (PSF), and polyvinylidene fluoride (PVDF); and the composite nanofiltration membrane is a flat membrane.
[0017] The present invention has the following outstanding technical advantages.
[0018] In the present invention, a mixed aqueous solution is prepared, including HA-CD, KCl and PIP. + The coordination interaction between HA-CD and PIP molecules induces the growth of KCl crystals, and the growth morphology of the crystals is optimized by the adjustable temperature setting, making it a template for interfacial polymerization reaction. A rough surface structure can be obtained by preparing the composite polyamide nanofiltration membrane on the crystal template, which increases the unit water permeability area of the membrane. In addition, the host-guest interaction between HA-CD and PIP molecules helps the functional layer to achieve a narrow pore size distribution, ensuring the high ion selectivity of the polyamide nanofiltration membrane. The composite polyamide nanofiltration membrane has excellent salt retention rate and permeation flux, wherein the retention rate of sodium sulfate can reach more than 98.5%, and the water flux can reach 14L / (m 2 ·h·bar) or above. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 It is a graph showing the changes in separation performance of the composite polyamide nanofiltration membranes of Examples 1-6 of the present invention.
[0020] Figure 2 It is a graph showing the separation performance changes of the composite polyamide nanofiltration membranes of Examples 7-12 of the present invention.
[0021] Figure 3 It is a graph showing the separation performance changes of the polyamide composite nanofiltration membranes of Examples 13-17 of the present invention.
[0022] Figure 4 It is a diagram showing the change in membrane surface roughness of the polyamide composite nanofiltration membrane of Examples 13-17 of the present invention.
[0023] Figure 5 This is a SEM image of the surface morphology of the composite polyamide nanofiltration membrane of Example 18 of the present invention.
[0024] Figure 6It is a pore size distribution diagram of the composite polyamide nanofiltration membrane in some embodiments of the present invention. DETAILED DESCRIPTION
[0025] The present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the specific embodiments are only used to explain and introduce the present invention and cannot limit the scope of application of the present invention. Any modifications and changes made to the present invention fall within the protection scope of the present invention without departing from the purpose and scope of the present invention.
[0026] Examples 1-6.
[0027] A method for preparing a high permeability polyamide nanofiltration membrane using a crystal template in this embodiment is carried out by the following steps:
[0028] Step 1: Weigh β-cyclodextrin-modified sodium hyaluronate (HA-CD) powder and place it in a conical flask, then add deionized water to dissolve it to obtain a HA-CD solution, wherein the mass concentration of the HA-CD solution is 0 to 1.0%.
[0029] Step 2: Weigh potassium chloride (KCl) powder and add it to the HA-CD solution, stir to dissolve it, and the mass volume concentration of KCl in the mixed solution is 6 g / L.
[0030] Step 3: Weigh piperazine monomer (PIP) and dissolve it in the above mixed solution to obtain a mixed aqueous phase solution, wherein the mass concentration of PIP is 0.4%.
[0031] Step 4: prepare a TMC oil phase solution using n-hexane solution, wherein the mass concentration of TMC is 0.1%.
[0032] Step 5: Immerse the polymer-based membrane in the PIP aqueous solution for 5 minutes and drain for 1 minute.
[0033] Step 6: Place the base film from the previous step in an oven for heat treatment. The temperature of the oven is set to 60° C. and the heat treatment time is 10 minutes.
[0034] Step 7: Pour the prepared TMC oil phase solution onto the surface of the base membrane in step 6 to carry out interfacial polymerization reaction. After a period of reaction, pour out the remaining unreacted TMC solution to obtain a primary polyamide nanofiltration membrane. The reaction time is 2 minutes.
[0035] Step 8: Heat treatment: Place the primary polyamide nanofiltration membrane obtained in step 7 in an oven for heat treatment. At this time, the temperature of the oven is set to 65° C. and the heat treatment time is 15 min to obtain a composite polyamide nanofiltration membrane.
[0036] Step nine, placing the composite polyamide nanofiltration membrane in deionized water for storage.
[0037] The above studies mainly investigated the effect of HA-CD concentration on the separation performance of composite nanofiltration membrane. Figure 1 shown.
[0038] Examples 7-12.
[0039] Step 1: Weigh β-cyclodextrin-modified sodium hyaluronate (HA-CD) powder and place it in a conical flask, then add deionized water to dissolve it to obtain a HA-CD solution, wherein the mass concentration of the HA-CD solution is 0.4%.
[0040] Step 2: Weigh potassium chloride (KCl) powder and add it to the HA-CD solution, stir to dissolve it, and the mass volume concentration of KCl in the mixed solution is 0-10 g / L.
[0041] Step 3: Weigh piperazine monomer (PIP) and dissolve it in the above mixed solution to obtain a mixed aqueous phase solution, wherein the mass concentration of PIP is 0.4%.
[0042] Step 4: prepare a TMC oil phase solution using n-hexane solution, wherein the mass concentration of TMC is 0.1%.
[0043] Step 5: Immerse the polymer-based membrane in the PIP aqueous solution for 5 minutes and drain for 1 minute.
[0044] Step 6: Place the base film from the previous step in an oven for heat treatment. The temperature of the oven is set to 60° C. and the heat treatment time is 10 minutes.
[0045] Step 7: Pour the prepared TMC oil phase solution onto the surface of the base membrane in step 6 to carry out interfacial polymerization reaction. After a period of reaction, pour out the remaining unreacted TMC solution to obtain a primary polyamide nanofiltration membrane. The reaction time is 2 minutes.
[0046] Step 8: Heat treatment: Place the primary polyamide nanofiltration membrane obtained in step 7 in an oven for heat treatment. At this time, the temperature of the oven is set to 65° C. and the heat treatment time is 15 min to obtain a composite polyamide nanofiltration membrane.
[0047] Step nine, placing the composite polyamide nanofiltration membrane in deionized water for storage.
[0048] The above studies mainly investigated the effect of KCl concentration on the separation performance of composite nanofiltration membranes. Figure 2 shown.
[0049] Examples 13-17.
[0050] Step 1: Weigh β-cyclodextrin-modified sodium hyaluronate (HA-CD) powder and place it in a conical flask, then add deionized water to dissolve it to obtain a HA-CD solution, wherein the mass concentration of the HA-CD solution is 0.4%.
[0051] Step 2: Weigh potassium chloride (KCl) powder and add it to the HA-CD solution, stir to dissolve it, and the mass volume concentration of KCl in the mixed solution is 6 g / L.
[0052] Step 3: Weigh piperazine monomer (PIP) and dissolve it in the above mixed solution to obtain a mixed aqueous phase solution, wherein the mass concentration of PIP is 0.4%.
[0053] Step 4: prepare a TMC oil phase solution using n-hexane solution, wherein the mass concentration of TMC is 0.1%.
[0054] Step 5: Immerse the polymer-based membrane in the PIP aqueous solution for 5 minutes and drain for 1 minute.
[0055] Step 6: Place the base film from the previous step in an oven for heat treatment. The temperature of the oven is set to 40-80° C. and the heat treatment time is 10 minutes.
[0056] Step 7: Pour the prepared TMC oil phase solution onto the surface of the base membrane in step 6 to carry out interfacial polymerization reaction. After a period of reaction, pour out the remaining unreacted TMC solution to obtain a primary polyamide nanofiltration membrane. The reaction time is 2 minutes.
[0057] Step 8: Heat treatment: Place the primary polyamide nanofiltration membrane obtained in step 7 in an oven for heat treatment. At this time, the temperature of the oven is set to 65° C. and the heat treatment time is 15 min to obtain a composite polyamide nanofiltration membrane.
[0058] Step nine, placing the composite polyamide nanofiltration membrane in deionized water for storage.
[0059] The above studies mainly investigated the effect of the change of KCl crystallization temperature on the separation performance of composite nanofiltration membrane. The results are shown in the attached Figure 3 shown.
[0060] Example 18
[0061] Step 1: Weigh β-cyclodextrin-modified sodium hyaluronate (HA-CD) powder and place it in a conical flask, then add deionized water to dissolve it to obtain a HA-CD solution, wherein the mass concentration of the HA-CD solution is 0.4%.
[0062] Step 2: Weigh potassium chloride (KCl) powder and add it to the HA-CD solution, stir to dissolve it, and the mass volume concentration of KCl in the mixed solution is 6 g / L.
[0063] Step 3: Weigh piperazine monomer (PIP) and dissolve it in the above mixed solution to obtain a mixed aqueous phase solution, wherein the mass concentration of PIP is 0.4%.
[0064] Step 4: prepare a TMC oil phase solution using n-hexane solution, wherein the mass concentration of TMC is 0.1%.
[0065] Step 5: Immerse the polymer-based membrane in the PIP aqueous solution for 5 minutes and drain for 1 minute.
[0067] Step 6: Place the base film from the previous step in an oven for heat treatment. The temperature of the oven is set to 60° C. and the heat treatment time is 10 minutes.
[0068] Step 7: Pour the prepared TMC oil phase solution onto the surface of the base membrane in step 6 to carry out interfacial polymerization reaction. After a period of reaction, pour out the remaining unreacted TMC solution to obtain a primary polyamide nanofiltration membrane. The reaction time is 2 minutes.
[0069] Step 8: Heat treatment: Place the primary polyamide nanofiltration membrane obtained in step 7 in an oven for heat treatment. At this time, the temperature of the oven is set to 65° C. and the heat treatment time is 15 min to obtain a composite polyamide nanofiltration membrane.
[0070] Step nine, placing the composite polyamide nanofiltration membrane in deionized water for storage.
Claims
1. A method for preparing a high permeability polyamide nanofiltration membrane using a crystal template, characterized in that Crystal template and functional layer: The crystal template comprises a mixed aqueous solution prepared by mixing β-cyclodextrin-modified sodium hyaluronate (HA-CD) powder, potassium chloride (KCl) powder and piperazine (PIP) monomer, immersing a basement membrane in the mixed aqueous solution for 5 minutes and draining for 1 minute; placing the basement membrane immersed in the aqueous solution in an oven for heat treatment to obtain a crystal template for 10 minutes; pouring an oil phase solution on the basement membrane forming the crystal template for interfacial polymerization reaction for 2 minutes; placing the membrane in an oven for heat treatment to obtain a composite polyamide nanofiltration membrane, the oven temperature is set to 65°C, and the heat treatment time is 15 minutes; the mass volume concentration of piperazine in the mixed aqueous solution is 0.4%; the mass volume concentration of piperazine in the oil phase solution is 0.1%.
2. A method for preparing a high permeability polyamide nanofiltration membrane using a crystal template according to claim 1, characterized in that The base membrane material is polyethersulfone.
3. The method for preparing a high permeability polyamide nanofiltration membrane using a crystal template according to claim 1, characterized in that The concentration of HA-CD in the mixed aqueous phase is 0-1.0%.
4. The method for preparing a high permeability polyamide nanofiltration membrane using a crystal template according to claim 1, characterized in that The concentration of KCl in the mixed water phase is 0-10 g / L.
5. The method for preparing a high permeability polyamide nanofiltration membrane using a crystal template according to claim 1, characterized in that The temperature of the crystal template heat treatment is 40-80°C.
6. The method for preparing a high permeability polyamide nanofiltration membrane using a crystal template according to claim 1, characterized in that The composite nanofiltration membrane is a flat membrane.
Citation Information
Patent Citations
Polyamide composite membrane prepared by using inorganic salt additive, and preparation and application thereof
CN110394069A
Method for preparing nanofiltration membrane based on thermally induced inorganic salt crystal growth
CN111921391A
Preparation method of beta-cyclodextrin modified sodium hyaluronate composite nanofiltration membrane
CN115770477A
Reverse osmosis membranes
GB1326489A